The Study of Relationship between the Knowledge and Attitude of Tuberculosis (TB) Patients about Drug Compliance at the Health Centre - Fauzi, Zulfa Ismaniar; Zulfikri, Zulfikri; Harefa, Inmariahni (Journal of Health Sciences and Epidemiology, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, which most often attacks various organs, especially the lungs. This study aimed to determine the relationship between knowledge and TB patients' attitudes toward compliance with tuberculosis drugs at the Helvetia Medan Health Center. This type of research used an analytical observational method with the cross-sectional approach. The sampling technique used was quota sampling, with 75 respondents. Data collection in this study used to form sheets in questionnaires given to respondents directly and data analysis using the chi-square test. The results showed that respondents with good knowledge were 29 respondents (38.7%), good enough 33 respondents (44%), not good enough 12 respondents (16%), and not good one respondent (1.3%). A good attitude was 23 respondents (30.7%), good enough 37 respondents (49.3%), not good enough 14 respondents (18.7%), and not good one respondent (1.3%). Obedient compliance to TB medication was 25 respondents (33.3%), quite obedient 33 respondents (44%), and less obedient 17 respondents (22.7%).  This study concluded that knowledge and attitude had a significant relationship with adherence to tuberculosis medication, with a knowledge p-value of 0.003 <0.05 and an attitude p-value of 0.037 <0.05. Healthcare professionals must employ innovative strategies to enhance knowledge and attitudes, raise public awareness, and ensure full compliance with the TB treatment program. It is crucial to implement this measure to mitigate the future prevalence of antibiotic resistance in treating tuberculosis.